Abraham’s Sacrifice in the Qur’an and the Bible: Comparative Hermeneutics of Narrative, Meaning, and Textual Authority - Andi, Azhari; Ridho, Moch. Taufiq (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2026)
This study examines the long-standing theological and exegetical debate over the identity of the intended sacrificial son in the story of Abraham’s sacrifice—Isaac or Ishmael— and its implications for interreligious relations. The study departs from the observation that much of the existing scholarship on Q. 37:99-113 and Genesis 22 is shaped by polemical and identity-driven readings that privilege communal supremacy and scriptural integrity, while common ethical interpretations are often neglected. Methodologically, this article employs a comparative hermeneutic that juxtaposes classical and contemporary Qur’anic exegesis with Jewish and Christian interpretations of the Aqedah. By tracing the diachronic development of Muslim, Jewish, and Christian exegetical traditions, the study identifies both the points of contestation and the areas of convergence in reading Abraham’s sacrifice. The article argues that, despite enduring disagreements regarding whether Isaac or Ishmael was the intended sacrifice, the three traditions share at least two major theological and ethical commitments: Abraham’s unwavering faith and obedience to God, and a principled rejection of human sacrifice as incompatible with divine justice. These shared principles acquire renewed significance in the context of ongoing religiously motivated conflicts, where sacred narratives are frequently mobilized to legitimize violence. By foregrounding a harmonious and ethically oriented reading of Abraham’s sacrifice, this study contributes to Qur’anic studies, comparative scripture, and interfaith dialogue. It suggests that the narrative can serve as a theological resource for peacebuilding and interreligious solidarity, while future research may further explore its application in peace education and liturgical practices.